2011
DOI: 10.1002/ibd.21494
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing thiopurine therapy in inflammatory bowel disease

Abstract: Despite recent advances, the therapeutic armamentarium for inflammatory bowel disease (IBD) is still limited. In addition, a step-up approach is recommended for most IBD patients. Thus, optimizing each medical therapy before switching to another drug class is the rule in clinical practice. Conventional therapies for IBD have not received the same amount of attention as biologic therapies over the last decade. However, due to their efficacy, safety, and low cost the thiopurine drugs azathioprine and 6-mercaptop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…Minimal TPMT activity can cause early, potentially life‐threatening myelosuppression in the setting of thiopurine use. Epidemiologic studies in the Caucasian population have shown a trimodal distribution of TPMT enzyme activity, with 89% having normal or high activity, 11% having intermediate activity, and 0.3% having minimal activity . The utility TPMT testing in personalizing thiopurine treatment has remained controversial in the Asian population.…”
Section: Resultsmentioning
confidence: 99%
“…Minimal TPMT activity can cause early, potentially life‐threatening myelosuppression in the setting of thiopurine use. Epidemiologic studies in the Caucasian population have shown a trimodal distribution of TPMT enzyme activity, with 89% having normal or high activity, 11% having intermediate activity, and 0.3% having minimal activity . The utility TPMT testing in personalizing thiopurine treatment has remained controversial in the Asian population.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the advent of anti-TNF agents, thiopurines remain the blackbone of IBD treatment. [1][2][3][4] In 2013, our therapeutic armenmatarium is still limited in IBD. Hence, optimizing available drugs is crucial when managing patients with IBD.…”
mentioning
confidence: 99%
“…19 There is a major body of evidence that metabolite levels of thiopurines (e.g., 6-TGN, 6-MMPR) differ substantially between patients, a phenomenon that cannot be explained exclusively by the TPMT polymorphism, therefore requiring alternative monitoring strategies. 10,24 By now, associations of 6-TGN levels in RBC have been restricted to clinical end points in patients with IBD with partly conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…17 A potential role for metabolite monitoring in optimizing the dosing regimens of thiopurine has been considered, but it is not currently recommended in clinical practice. 18,19 To date, evidence concerning the prognostic value of thiopurine metabolite exposure is restricted to the prediction of clinical recurrence. The relationship between endoscopic improvement under azathioprine therapy and metabolite concentrations remains unknown.…”
mentioning
confidence: 99%